ANALISIS RASIO CAR,ROA,ROE DAN BOPO TERHADAP KONDISI FINANCIAL DISTRESS PADA BANK UMUM SYARIAH PERIODE 2019-2020: ANALISIS RASIO CAR,ROA,ROE DAN BOPO TERHADAP KONDISI FINANCIAL DISTRESS PADA BANK UMUM SYARIAH PERIODE 2019-2020 - Depi NopitaRati; Eka Sri Wahyuni; Debby Arisandi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
This study intends to decide the impact of the Capital and Operating Income (BOPO) on the Financial Distress state of Islamic Commercial Banks 2019-2020. This sort of exploration is quantitative with an unmistakable methodology. The example utilized in this study was 10 Islamic business banks enlisted with the Financial Services Authority (OJK) in the 2019-2020 period. The information assortment strategy is finished by getting to the yearly monetary reports distributed by the Financial Services Authority. The information examination procedure utilized was the board information relapse investigation strategy. The consequences of this study show that the CAR variable fundamentally affects monetary misery with a sig worth of 0.016 < 0.05, ROA essentially affects monetary pain with a sig worth of 0.023 < 0.05, ROE essentially affects monetary trouble with a sig worth of 0.020 < 0.05. , BOPO essentially affects monetary misery with a sig worth of 0.019 <0.05.